Phenothiazinium Dyes Are Active against Trypanosoma cruzi In Vitro. (4th July 2019) - Bulhões Portapilla, Gisele; Pereira, Luiz Miguel; Bronzon da Costa, Cássia Mariana; Voltarelli Providello, Maiara; Sampaio Oliveira, Pedro Alexandre; Goulart, Amanda; Ferreira Anchieta, Naira; Wainwright, Mark; Leite Braga, Gilberto Úbida; de Albuquerque, Sérgio
Abstract : Chagas disease is a tropical illness caused by the protozoan Trypanosoma cruzi . The disease affects populations of the Americas and has been spread to other continents due to the migration process. The disease is partially controlled by two drugs, Benznidazole and Nifurtimox. These molecules are active in the acute phase of the infection but are usually ineffective during the symptomatic chronic phase. Several research groups have developed novel candidates to control Chagas disease; however, no novel commercial formulation is available. In this article, we described the anti- T. cruzi effects of phenothiazinium dyes in amastigote and trypomastigote forms of the parasite. Methylene Blue, New Methylene Blue, Toluidine Blue O, and 1, 9-Dimethyl Methylene Blue inhibited the parasite proliferation at nanomolar concentrations and also demonstrated low toxicity in host cells. Moreover, combinations of phenothiazinium dyes indicated a synergic pattern against amastigotes compared to the Benznidazole counterparts. Phenothiazinium dyes levels of reactive oxygen species (ROS) and decreased the mitochondrial potential in trypomastigotes, indicating the mechanism of action of the dyes in T. cruzi . Our article offers a basis for future strategies for the control of Chagas disease using low-cost formulations, an important point for endemic underdeveloped regions.